Comparison of the Side Effects of Chlorhexidine and Honey Mouthwash among Dental Patients: A Randomized Controlled Trial: Side Effects of Chlorhexidine and Honey - Abid, Muhammad; Rauf, Rabia; Siddiq, Afshan; Mazhar, Samreen; Zaidi, Hasan Afaq; Zafar, Urooj (Pakistan Journal of Health Sciences, 2025)
Gingivitis, primarily caused by bacterial plaque buildup, was managed through mechanical removal, though this requires consistency. Chemical agents like chlorhexidine mouthwash were effective but have notable side effects. Honey, with its antibacterial properties, offers a potential alternative with fewer adverse effects. Objective: To compare the side effects of 0.12% chlorhexidine gluconate and 10% honey mouthwash to determine which offers a safer and more comfortable option for oral hygiene in young adults. Methods: This randomized controlled trial was conducted from June 2020 to December 2020 to compare the side effects of two oral care solutions, 0.12% chlorhexidine gluconate and 10% honey mouthwash, among young adults. Sixty subjects were recruited from the Department of Periodontology at a tertiary care hospital in Karachi. The primary focus of the study was to observe and document any side effects associated with each mouthwash during and after three weeks of usage for plaque removal and gingival health. Results: The study revealed that participants in Group A (chlorhexidine) reported a higher incidence of adverse effects, including a pronounced bad taste, numbness in the mouth, and noticeable tooth discoloration. In contrast, Group B (honey) participants generally reported a pleasant taste, with significantly fewer and milder side effects. Conclusions: Honey mouthwash offers a more comfortable user experience with fewer negative side effects, including a pleasant taste. This makes it a promising alternative for individuals seeking an effective and gentle approach to maintaining oral health.